A comparative study of functional outcome of treatment of intra-articular fractures of distal end radius fixed with external fixator vs. volar plate - Mahi, Gagandeep; Yogi, Lokesh Kumar (International Journal of Research in Orthopaedics, 2019)
Background: Distal end radius fractures constitute 75% of all forearm fractures. Maintenance of the articular congruity is an ardent prerequisite for successful recovery, following distal end radius fractures. The available options include immobilization with plaster, external fixation, prefabricated splintage using ligamentotaxis, K-wire fixation, and open reduction internal fixation with various plates. The aim of the study was to analyze and compare the functional outcome and possible complications associated with fixation of two different surgical modalities: External fixator and Volar Plate in the treatment of intra-articular fractures of distal end radius. Methods: A prospective comparative study was conducted in 26 patients who were admitted and operated between September 2017 to September 2018 and had fulfilled the inclusion /exclusion criteria. They were allocated into 2 groups-group A and B, 13 patients each for external fixator and open reduction and internal fixation with volar T plate, respectively. Results: The results were assessed using the modified Green O’ Brien Scoring. In Group-A of patients treated with External fixator we had 6 excellent, 3 good, 3 fair results and 1 poor results. Whereas in Group-B of ORIF with Volar plating we had 7 excellent, 3 good, 2 fair results and 1 poor results. Conclusions: In our study, volar plate fixation showed superiority as it provides better long term functional outcome owing to more adequate restoration of radio-ulnar variance and distal end radius parameters.